(3GdEjVGM aj Gdhba hGdEHJOGAs - (3eMeO Hf GdbGSe Hf HTGQ GdGfHGQj GdfMhj, CHh HcQ,J (B328 (3g` s
(3ChdgG (B:s
(3YRjR dGjCJjg GdHGWd ef Hjf jOjg hdG ef Ndag bGd QShd Gddg Udi Gddg Ydjg hSde(B: (3jbhd Gddg YR hLd(B: (3ef TZdg bQGAI GdbQBf Yf OYGFj heSCdJj CYWjJg CaVd KhGH GdTGcQjf s
(3BNQgG (B:s
(3jfJgj CKfGA GdcdGe aj ShQI (B"(3JnHJ(B" (3hBNQ eG ajg (B: (3hMHd ef eSO (B: (3hgh GdSdSdI GdJi aj GdfGQ hbGd bhe(B: (3gh dja Gdoebd,hbGd CHhYHjOI GdeSO YfO GdYQH(B: (3MHGd Jchf ef VQhH s
(3GdfSNI HgG MhGTs
(3fSNI SGOSIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B334s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B210s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs